Association of Physical Fitness and Motor Competence with Health and Well-Being in Children and Adolescents - Drenowatz, Clemens; Greier, Klaus (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Available research has indicated a decline in physical fitness and motor competence over the last several decades. Movement restrictions and policies that have emphasized social distancing, due to the recent COVID-19 pandemic, may have further increased the prevalence of youth with insufficient physical fitness and motor competence. As physical fitness and motor competence are critical contributors to an active and healthy lifestyle, it is important to re-emphasize their role in the general health and development of children and adolescents and, accordingly, future public health. Particularly with the re-opening of schools, sports clubs and public parks, the promotion of activities that enhance physical fitness and motor competence in children and adolescents is warranted. This reprint highlights the importance of physical fitness and motor competence for the health and well-being of children and adolescents, by providing an interdisciplinary platform for research addressing this topic.